2009
DOI: 10.1002/ca.20804
|View full text |Cite
|
Sign up to set email alerts
|

Eagle's syndrome: A review of the literature

Abstract: Eagle's syndrome represents symptoms brought on by compression of regional structures by elongation of the styloid process or ossification of the stylohyoid or stylomandibular ligaments. Watt Eagle described it for the first time in 1937, dividing it into two subtypes: the "classic syndrome" and the "stylo-carotid artery syndrome." Many theories have been put forth regarding its pathogenesis. Depending on the underlying pathogenetic mechanism and the anatomical structures compressed or irritated by the styloid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
235
1
57

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(296 citation statements)
references
References 112 publications
3
235
1
57
Order By: Relevance
“…On neurological examination, left central facial paralysis and left hemiparesia were found. Eagle syndrome is a rare clinical entity and described as an elongated styloid process or mineralization of the stylohyoid or stylomandibular ligaments that causes cervical and facial pain, sensation of foreign body lodged in the pharynx, dysphagia and odynophagia (7,10,19). The normal length of the adult styloid in an adult is thought to be approximately 2.5 cm while an elongated styloid is considered >3 cm.…”
Section: Casementioning
confidence: 99%
“…On neurological examination, left central facial paralysis and left hemiparesia were found. Eagle syndrome is a rare clinical entity and described as an elongated styloid process or mineralization of the stylohyoid or stylomandibular ligaments that causes cervical and facial pain, sensation of foreign body lodged in the pharynx, dysphagia and odynophagia (7,10,19). The normal length of the adult styloid in an adult is thought to be approximately 2.5 cm while an elongated styloid is considered >3 cm.…”
Section: Casementioning
confidence: 99%
“…The incidence varies by report. Review of literature reveals wide range of reported incidence styloid elongation from 3% to as high as 28% with most of these people being asymptomatic [4]. Incidental findings have increased with increasing radiograph use.…”
Section: Discussionmentioning
confidence: 99%
“…It is possibly an anatomic variant vs. post traumatic calcification. Some have reported association with posttonsillectomy patients; it is suggested to be related to granulation tissue and scar formation around the bone trapping nearby nerves [4]. Symptoms depend not only on length, but also width and projection of the styloid [4,5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations